The empowerment of the Karunia Mandiri Joint Business Group in increasing production and sales - Anissa Hakim Purwantini; Nur Ita Ariansy; Saraswati Novi Yuliantoputri; Bayu Hermawan; Muhammad Humam Abror; Achmad Faisal Alfarazi (Universitas Muhammadiyah Magelang, 2021)
Karunia Mandiri Joint Business Group (KUBE) is located in Pakeron Hamlet, Sumberarum Village, Tempuran District, Magelang Regency which produces traditional Magelang food, namely cassava emplek. The problems faced by KUBE are less than optimal marketing and the use of manual production tools. The purpose of the community service is to improve the quality of KUBE human resources in managing its business, which includes marketing, financial management, and production so as to increase production and sales. The method is to provide training and mentoring. The result of this service is more optimal marketing with the appearance of new products through rebranding and packaging as well as the use of digital marketing. Then, the production process is better with appropriate technology for molding dough and applying hygiene standards. In addition, financial management is more organized with simple bookkeeping and accounting so that selling prices can be competitive and profits can be identified.